2022
DOI: 10.7717/peerj.13463
|View full text |Cite
|
Sign up to set email alerts
|

Embedding the value of coastal ecosystem services into climate change adaptation planning

Abstract: Coastal habitats, such as salt marshes and dune systems, can protect communities from hazards by reducing coastline exposure. However, these critical habitats and their diverse ecosystem services are threatened by coastal development and the impacts from a changing climate. Ever increasing pressure on coastal habitats calls for coastal climate adaptation efforts that mitigate or adapt to these pressures in ways that maintain the integrity of coastal landscapes. An important challenge for decisionmakers is dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
3
0
2
Order By: Relevance
“…adaptations, the rate of present-day climate change is much greater than historical change and remains a key threat to the continued viability of sea turtle populations globally (Fuentes et al, 2011;Hamann et al, 2007;Patrício et al, 2021). Although many studies have used the InVEST Coastal Vulnerability Model (e.g., Arkema et al, 2013;Onat et al, 2018;Wedding et al, 2022;Zhang et al, 2021), or a similar index-based approach (e.g., Pantusa et al, 2018;Pendleton et al, 2004), to examine the broadscale coastal vulnerability of human populations and their infrastructure, relatively few studies have considered coastal species and their nesting habitats (see de Vos et al, 2019;Von Holle et al, 2019). Using the InVEST model, we found that, while vulnerability varied across nesting beaches, vulnerability was generally higher for beaches with more nesting activity.…”
Section: Rankmentioning
confidence: 99%
“…adaptations, the rate of present-day climate change is much greater than historical change and remains a key threat to the continued viability of sea turtle populations globally (Fuentes et al, 2011;Hamann et al, 2007;Patrício et al, 2021). Although many studies have used the InVEST Coastal Vulnerability Model (e.g., Arkema et al, 2013;Onat et al, 2018;Wedding et al, 2022;Zhang et al, 2021), or a similar index-based approach (e.g., Pantusa et al, 2018;Pendleton et al, 2004), to examine the broadscale coastal vulnerability of human populations and their infrastructure, relatively few studies have considered coastal species and their nesting habitats (see de Vos et al, 2019;Von Holle et al, 2019). Using the InVEST model, we found that, while vulnerability varied across nesting beaches, vulnerability was generally higher for beaches with more nesting activity.…”
Section: Rankmentioning
confidence: 99%
“…Tal destaque nas produções estadunidenses pode ser justificado pelas sérias repercussões em curso nas áreas costeiras metropolitanas (KARAMOUZ, ZOGHI, MAHMOUDI, 2022). Para Wedding et al (2022), essa pressão cada vez maior sobre os habitats costeiros exige esforços de adaptação e mitigação para proteger vidas e propriedades humanas.…”
Section: Países Dos Estudos De Casounclassified
“…Os resultados da análise indicaram que os centros urbanos podem ter perdido grandes porções de habitats costeiros naturais devido à urbanização e fatores como a mudança no fluxo natural da água, poluição e introdução de espécies exótica. Wedding et al (2022) determinaram o papel do habitat natural na redução da exposição à erosão e inundação no condado de Marin, Califórnia, utilizando um modelo de vulnerabilidade costeira (InVEST). Os autores realizaram a modelagem de serviços ecossistêmicos para determinar o papel do habitat natural na proteção costeira, identificando quais destes devem ser priorizados para restauração a fim de reduzir o risco para as pessoas, propriedades e para os próprios ecossistemas.…”
Section: Simulaçõesunclassified
“…Furthermore, assessment of the value of ecosystem services can help in the preservation of natural resources [ 5 ]. Ecosystem services are of paramount importance in adapting and mitigating the effects of climate change [ 6 ]. Forests play a crucial role in mitigating climate change by sequestering carbon dioxide, regulating local and regional climates, and minimizing the likelihood of natural disasters [ 3 ].…”
Section: Introductionmentioning
confidence: 99%